Civil-Military Relations, Democratic Consolidation and Civilian Control: Insights from South Korea's Experience and Prospects for Thailand - Wannawit, Ratchada (My University, 2025)
The thesis focuses on civil-military relations (CMR), democratic consolidation, and civilian control in the Republic of Korea (ROK), especially during Roh Tae-woo and Kim Young-sam’s presidencies in the Sixth Republic. This transitional period shifted the ROK from authoritarianism to democracy, offering a valuable case for examining these developments. Therefore, this study aims to explore and analyze the impact of the 9th constitutional amendment on CMR, democratic consolidation, and civilian supremacy in the ROK, including how military reforms during the Roh and Kim administrations affected these elements, as well as the prospects for Thailand. The primary sources for thesis include English-language secondary literature and qualitative data, including Thai sources on democratic consolidation in the ROK and an interview with a Thai scholar to support the arguments. The study found that the 9th constitutional amendment provided a legal foundation for establishing democratic consolidation and civilian control, while the military reforms, making the armed forces more accept the authority of the civilian president. To improve CMR, democratic consolidation, and civilian supremacy in Thailand, the mission of the Ministry of Defense must be reexamined, and the state should separate the monarchy from national security.
Keywords: Civil-Military Relation, Democratic Consolidation, Civilian Control, The Republic of Korea, Thailand